Case report: Mycobacterium neoaurum infection during ICI therapy in a hepatocellular carcinoma patient with psoriasis - Pang, Ling; Chen, Zhongju; Xu, Dong; Cheng, Weiting (Frontiers in Immunology, 2022)
We report here a patient with advanced hepatocellular carcinoma (HCC) and psoriasis treated with immune checkpoint inhibitor (ICI) therapy (camrelizumab) who experienced tumor partial response and psoriatic exacerbation. Surprisingly, the patient also infected mycobacterium neoaurum without immunosuppression, while it was an opportunistic infection and mainly happened in the immunosuppressed patients. We discussed the possibility that this infection was an ICI-associated infection independent of immunosuppression due to dysregulated immunity, which was the result of the effects of immunotherapy and autoimmune disease (AID), and the characteristics and treatment of M. neoaurum, which was rarely reported in China. This case highlights the fact that some infections can be precipitated by ICIs in the absence of immunosuppressive treatment, especially the patients with AID.